Genetic diversity and phylogenetic relationship of German cockroaches, Blattella germanica (L.) (Blattodea: Ectobiidae) from urban commercial spaces - Nurul Akmar Hussin; Li, Lim; Wan Aisyah Natasya Wan Gidi Sairee; Hussein Ali Baiqr; Martini Martini; Retno Hestiningsih; Sri Yuliawati; Ameilia Zuliyanti Siregar; Abdul Hafiz Ab Majid (Penerbit Universiti Kebangsaan Malaysia, 2025)
Infestations of German cockroach (Blattella germanica) pose a significant threat to public health and the economy. Understanding its population's genetic diversity can improve pest control strategies to tackle this resilient pest. Therefore, this study focused on the genetic analysis of several populations of B. germanica collected from urban commercial spaces in Penang, Malaysia. Five urban commercial spaces, comprising restaurants and shopping centres, were selected from Bukit Mertajam, Juru, Bayan Lepas, and Gelugor. A total of 30 isolates were collected, and fragments of the mitochondrial cytochrome c oxidase subunit I (COI) gene and the 16S rRNA gene were amplified and sequenced. Genetic analysis revealed the formation of two haplotypes, separating B. germanica populations from shopping complexes and restaurants, with slightly higher nucleotide diversity observed in populations from shopping centers. Phylogenetic analysis using the Neighbor-Joining method also supported the observed separation between populations from restaurants and shopping centers. These findings suggest that the population genetics of B. germanica in urban areas is influenced by human-mediated activities, reflecting their adaptability and ongoing evolution. This indirectly underscores the significance of refining the integrated pest management (IPM) strategies for more effective pest control in high-traffic commercial areas.